PWE-096 Rectal hypersensitivity in IBS: A systematic review and meta-anlaysis. (June 2019) - Roberts, Christopher; Albusoda, Ahmed; Aziz, Qasim
Abstract : Introduction: Rectal hypersensitivity is defined as being an exaggerated response to painful rectal stimuli and is thought to occur in Irritable Bowel Syndrome (IBS) although it is not a universal observation. The aim of this systematic review and meta-analysis is to confirm the presence and determine how common rectal hypersensitivity is in IBS and to determine if there are other factors such as IBS criteria, age, gender and IBS subtype that affect the presence of rectal hypersensitivity. Secondary aims were to see if rectal hypersensitivity was present in IBD to see if inflammation plays a key role in rectal hypersensitivity hence a second meta-analysis was performing assessing rectal hypersensitivity in IBD. Methods: A systematic review of the literature from MEDLINE and EMBASE databases (1970-Present) was carried out. Only prospective studies were included that compared pain or discomfort thresholds to mechanical rectal stimuli in an IBS and a control population. The second review looked at studies that measured pain or discomfort thresholds to mechanical rectal stimuli in an IBD and a control population. Data was pooled for both meta-analyses and Hedges g effect sizes were calculated with 95% confidence intervals (CIs). This review is registered with PROSPERO (CRD42018095687). Results: The search strategy identified 684 studies of which 70 were deemed relevant and 31 studies met the inclusion criteria. Rectal sensitivity was greater in an IBS population compared to controls. The effect size calculated was 0.966 95% CIs (0.76–.166) (p<0.0001). Significant heterogeneity was seen (I 2 = 77.2%). Secondary analysis revealed that gender, IBS subtype and IBS criteria did not have a significant impact upon the presence of rectal hypersensitivity. When comparing adult and paediatric IBS populations there was a significant difference. There was no statistically significant difference between IBD and healthy controls 0.456 95% CIs (-0.20–.119) (p=0.178) (I 2 =87.6%). However, a significant difference when comparing those with active flares of their IBD against those studies that used quiescent IBD was found. Conclusions: Rectal hypersensitivity is more common in an IBS population compared to controls. This indicates that pain sensation is altered in an IBS population and confirms that an altered rectal pain threshold is a marker of IBS. Rectal hypersensitivity is not a phenomenon normally present in IBD except during active flares of the diseases. The mechanisms behind rectal hypersensitivity are not fully understood but are likely due to a combination of peripheral and central factors that require further study to develop mechanism-based management approaches. However, it is unlikely that rectal hypersensitivity that likely occurs in IBS is due to the low-grade inflammatory burden.